Go4FutureSkills - a Comprehensive Competency Assessment Tool - Dorota Kwiatkowska-Ciotucha; Urszula Załuska (Ekonometria)
The aim of the article is to analyse the possibility of using the elements of a multidimensional comparative analysis in order to create a tool enabling a comprehensive assessment of a person's competencies, and comparing it with the requirements set in a specific vocational situation. An illustration of such possibilities is the presentation of a tool for assessing competencies prepared under the international Go4FutureSkills project. A competency profile was defined as a set of desirable competencies with the level of knowledge or skills required for a given profession/position assigned to each of them. The competency matrix created in this way serves as a basis for the comparison of the results obtained by the people using the tool. In its present form, this tool can be used by students and graduates majoring and specialising in logistics, as well as by employees from the logistics industry.(original abstract)